A two dimensional silicon detectors array for quality assurance in stereotactic radiotherapy: MagicPlate‐512. Issue 9 (22nd August 2014) - Aldosari, A. H.; Petasecca, M.; Espinoza, A.; Newall, M.; Fuduli, I.; Porumb, C.; Alshaikh, S.; Alrowaili, Z. A.; Weaver, M.; Metcalfe, P.; Carolan, M.; Lerch, M. L. F.; et al.
Abstract : Purpose: : Silicon diode arrays are commonly implemented in radiation therapy quality assurance applications as they have a number of advantages including: real time operation (compared to the film) and high spatial resolution, large dynamic range and small size (compared to ionizing chambers). Most diode arrays have detector pitch that is too coarse for routine use in small field applications. The goal of this work is to characterize the two‐dimensional monolithic silicon diode array named "MagicPlate‐512" (MP512) designed for QA in stereotactic body radiation therapy (SBRT) and stereotactic radio surgery (SRS). Methods: : MP512 is a silicon monolithic detector manufactured on a p ‐type substrate. An array contains of 512 pixels with size 0.5 × 0.5 mm 2 and pitch 2 mm with an overall dimension of 52 × 52 mm 2 . The MP512 monolithic detector is wire bonded on a printed circuit board 0.5 mm thick and covered by a thin layer of raisin to preserve the silicon detector from moisture and chemical contamination and to protect the bonding wires. Characterization of the silicon monolithic diode array response was performed, and included pixels response uniformity, dose linearity, percent depth dose, output factor, and beam profiling for beam sizes relevant to SBRT and SRS and depth dose response in comparison with ionization chamber. Results: : MP512 shows a good dose linearity (R 2 = 0.998) and repeatability within 0.2%. The measured depth dose response for field size of 10 × 10 cm 2 agreed to within 1.3%, when compared to a CC13 ionization chamber for depths in PMMA up to 30 cm. The output factor of a 6 MV Varian 2100EX medical linac beam measured by MP512 at the isocenter agrees to within 2% when compared to PTW diamond, Scanditronix point EDD‐2 diode and MO Skin detectors for field sizes down to 1 × 1 cm 2 . An over response of 4% was observed for square beam size smaller than 1 cm when compared to EBT3 films, while the beam profiles (FWHM) of MP512 match to within 2% the data measured by radiochromic film. Conclusions: : The response of the 2D detector array, MP512, has been evaluated. The properties of the array demonstrated suitability for use as in phantom dosimeter for QA in SRS and SBRT. Although MP512 matches film measurements down to 1 × 1 cm 2 well, it showed a discrepancy of 4% in the determination of output factors of beams smaller than 0.5 × 0.5 cm 2 due to the field perturbation generated by the large amount of silicon surrounding the central diode. MP512 is highly capable of measuring beam size (FWHM) and has a discrepancy of less than 1.3% when compared to EBT3 film. A reduction in the detector pitch to less than 2 mm would improve the penumbra reconstruction accuracy at the cost readout electronics complexity.